The antagonistic effect of phenolic compounds on ligninolytic and cellulolytic enzymes of ganoderma boninense, causing basal stem rot in oil palm - Surendran, Arthy; Siddiqiu, Yasmeen; Mohd Saud, Halimi; Manickam, Sivakumar; Syd Ali, Nusaibah (Friends Science Publishers, 2017)
Ganoderma sp. is a white-rot fungus and the causal pathogen of basal stem rot (BSR) in oil palm. To identify a potential chemical control for Ganoderma ten naturally occurring plant phenolic compounds, namely benzoic acid, curcumin, 2,6-dimethoxyl benzoic acid, 2,6-dimethoxyl phenol, guaiacol, ferulic acid, pyrocatechol, salicylic acid, syringic acid and vanillic acid were assessed for their antagonistic effect on Ganoderma as well their effect on the secretion of wood-degrading enzymes. Mycelial inhibition was dose dependent in each experiment and ranged from 4.4% to 100%. All the phenolic compounds except ferulic acid completely inhibited the growth of Ganoderma in a ‘poisoned food’ test using the range of concentrations that were tested. However, liquid media cultures containing low concentrations of phenolic compounds showed increased biomass production. Microscopic observations revealed that mycelia growing on media containing phenolic compounds showed deterioration. A significant decrease in the production of ligninolytic enzymes, as well as cellulose, amylase and xylanase was identified. The in vitro tests revealed that benzoic acid had the greatest inhibitory effect. The selected phenolic compounds inhibited the growth as well as the production of wood degrading enzymes indicating their potential use as chemical controls against Ganoderma for disease management of BSR.